Design of a New 3D Gelatin—Alginate Scaffold Loaded with Cannabis sativa Oil - Antezana, Pablo Edmundo (2022)
There is an increasing medical need for the development of new materials that could replace damaged organs, improve healing of critical wounds or provide the environment required for the formation of a new healthy tissue. The three-dimensional (3D) printing approach has emerged to overcome several of the major deficiencies of tissue engineering. The use of Cannabis sativa as a therapy for some diseases has spread throughout the world thanks to its benefits for patients. In this work, we developed a bioink made with gelatin and alginate that was able to be printed using an extrusion 3D bioprinter. The scaffolds obtained were lyophilized, characterized and the swelling was assessed. In addition, the scaffolds were loaded with Cannabis sativa oil extract. The presence of the extract provided antimicrobial and antioxidant activity to the 3D scaffolds. Altogether, our results suggest that the new biocompatible material printed with 3D technology and with the addition of Cannabis sativa oil could become an attractive alternative to common treatments of soft-tissue infections and wound repair.